Questionnaire Survey Results on Lifestyle Habits (Drinking, Smoking, Suppliant Intake, Exercise Habits, Sleep Time) of 20 Elderly People (Global Journal of Medical Research, 2023)
Du to COVID-19, which started in 2020, Japanese people have continued to live in selfrestraint until today. As a result, lifestyle habits have drastically changed. There are concerns about living indoors rather than going out, lack of exercise, increased alcohol consumption, irregular eating habits, and lack of sleep or excess sleep. In June 2022, we were finally able to hold a small number of health classes, and we conducted a questionnaire survey on the current living situation so that we will report the results. Participants were 20 elderly females who had been informed about the study and agreed to a consent form. Participants measured their height, weight, blood pressure, and completed a self-reported questionnaire. The content of the self-reported questionnaire survey was the smoking habit, drinking habit, exercise habit, sleeping time, and supplement intake. Participants were also asked about co-habitation.
Keywords: questionnaire survey; drinking; smoking; exercise habits; sleep time